2020
DOI: 10.1038/s41564-020-00846-z
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2 RNA–protein interactome in infected human cells

Abstract: Characterizing the interactions that SARS-CoV-2 viral RNAs make with host cell proteins during infection can improve our understanding of viral RNA functions and the host innate immune response. Using RNA antisense purification and mass spectrometry, we identified up to 104 human proteins that directly and specifically bind to SARS-CoV-2 RNAs in infected human cells. We integrated the SARS-CoV-2 RNA interactome with changes in proteome abundance induced by viral infection and linked interactome proteins to cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
347
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 289 publications
(400 citation statements)
references
References 108 publications
(149 reference statements)
24
347
0
3
Order By: Relevance
“…1C, Supplementary Table 1). Proteins recently identified in genome-wide interactome studies as direct RNA interaction partners for SARS-CoV-2 were selected for downstream functional characterization 3,[20][21][22] . Several of these have been shown to play a role in RNA processing, including splicing (such as HNRNPs F, H1, and H2), RNA trimming (POP1) and RNA decay (ZAP) [23][24][25] .…”
Section: Sars-cov-2 Prf Rna Capture Identifies Novel Host Interactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…1C, Supplementary Table 1). Proteins recently identified in genome-wide interactome studies as direct RNA interaction partners for SARS-CoV-2 were selected for downstream functional characterization 3,[20][21][22] . Several of these have been shown to play a role in RNA processing, including splicing (such as HNRNPs F, H1, and H2), RNA trimming (POP1) and RNA decay (ZAP) [23][24][25] .…”
Section: Sars-cov-2 Prf Rna Capture Identifies Novel Host Interactorsmentioning
confidence: 99%
“…Global analyses of RNA-and protein-interaction networks have increased our understanding of SARS-CoV-2 viral replication in a short time 2,3 . However, there is a lack of detailed mechanistic understanding of the interplay between RNA-protein complexes, which could inform the design of novel antivirals.…”
Section: Introductionmentioning
confidence: 99%
“…Target sequence preferences of APOBEC proteins are observed in our mutational profile, where the 5 out of 7 highest normalized mutational counts on C>U distributes along 5’-UC-3’ and 5’–CC–3’ motifs (Figure 2A) . It is also experimentally found that A1CF RNA editing cofactor, which is APOBEC1 complementation factor, is among the SARS-CoV-2 RNA binders (Schmidt et al, 2020) that strengthens the hypothesis of APOBEC proteins’ activity on the C>U substitutions.…”
Section: Resultsmentioning
confidence: 54%
“…Proteomic studies further showed that SARS-CoV-2 reshapes cellular translation, splicing, carbon metabolism, protein homeostasis, and nucleic acid metabolism [143]. In addition to viral proteins, it was shown that SARS-CoV-2 RNA directly and specifically binds and/or modulates a broad network of human proteins in infected human cells [145], and host mitochondria serve as an organelle platform for anti-SARS-CoV-2 immunity [146].…”
Section: Virus-host Interaction and Exploitation Of The Cellular Machinerymentioning
confidence: 99%